Bet the farm : the dollars and sense of growing food in America - Hoffman, Beth (Island Press, 2021)
Beth Hoffman was living the good life: she had a successful career as a journalist and professor, a comfortable home in San Francisco, and plenty of close friends and family. Yet in her late 40s, she and her husband decided to leave the big city and move to his family ranch in Iowa--all for the dream of becoming a farmer, to put into practice everything she had learned over decades of reporting on food and agriculture. There was just one problem: money. Half of America's two million farms made less than $300 in 2019. Between rising land costs, ever-more expensive equipment, the growing uncertainty of the climate, and few options for health care, farming today is a risky business. For many, simply staying afloat is a constant struggle. Bet the Farm chronicles this struggle through Beth's eyes as a beginning farmer. She must contend with her father-in-law, who is reluctant to hand over control of the land. Growing oats is good for the environment but ends up being very bad for the wallet. And finding somewhere, in the midst of COVID-19, to slaughter grass-finished beef is a nightmare. The couple also must balance the books, hoping that farming isn't a romantic fantasy that takes every cent of their savings. Even with a decent nest egg and access to land, making ends meet at times seems impossible. And Beth knows full well that she is among the privileged. If Beth can't make it, how can farmers who confront racism, lack access to land, or don't have other jobs to fall back on? Bet the Farm is a first-hand account of the perils of farming today and a personal exploration of more just and sustainable ways of producing food.--END FLAP.